A photocurable film composition and its application
By using a photocured film composition that replaces cycloalkyl acrylate, chain acrylate and aromatic acrylate, the existing packaging composition has been solved by solving the problem of excessive dielectric constant, aging resistance and insufficient bendability of the existing packaging composition. It realizes a packaging film with low dielectric properties, excellent bending resistance and high electrical insulation.
Patent Information
- Application Number
- CN202411407935.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-10
AI Technical Summary
The dielectric constant of the existing packaging composition is too high, making it difficult to meet the requirements of semiconductor devices for low dielectric performance, and there are problems such as aging resistance and insufficient bendability.
The photocuring film composition using fluorine-substituted cycloalkyl acrylate, chain acrylate and aromatic acrylate is prepared by photocuring reaction to obtain excellent curing rate, light transmittance, bending resistance and low dielectric constant. Encapsulation film.
It achieves the reduction of the dielectric constant, improves the stability and flexibility of the material, enhances the bending resistance of the film and electrical insulation, thereby extending the life and stability of the device.
Smart Images

Figure CN118909553B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a photocurable material, in particular to a photocurable film composition and application thereof. Background Art
[0002] Different from the light-emitting mechanism of the backlight of traditional LCD, organic electroluminescent devices (OLED) emit light through organic light-emitting materials with electroluminescent properties. As a new generation of display light-emitting devices, organic electroluminescent devices have the advantages of self-luminescence, low power consumption, high contrast, high response rate, bendability and low cost. At present, they are replacing LCDs in the fields of mobile phones, TVs and smart wearables to become the most widely used display devices, and have great development potential.
[0003] However, OLED display devices are currently at a disadvantage compared to other display technologies in terms of lifespan. The main reason is that the light-emitting materials in OLED devices will be seriously damaged after contacting with moisture and oxygen in the external environment, causing the device to have bad pixels or even a completely black screen that cannot be used, thereby reducing the lifespan of OLED display devices. Therefore, the packaging material is required to have good barrier properties and aging resistance to increase the lifespan of the device. With the gradual popularization of bendable mobile phones, higher requirements are also placed on the bendability of packaging materials.
[0004] At the same time, OLED devices also include other functional devices such as touch conductive layers, and the various electrical signals emitted by them also have an adverse effect on the OLED light-emitting layer. In addition, various static electricity and electromagnetic waves from the outside world may also cause OLED display devices to malfunction or reduce their lifespan. The use of packaging materials with lower dielectric constants can effectively improve electrical insulation and ensure the normal operation of display devices.
[0005] However, the dielectric constant of some existing encapsulation compositions is above 3.0, which is difficult to meet the requirements of semiconductor devices for low dielectric properties, and the disclosed low dielectric constant encapsulation compositions still have various problems and cannot meet the actual application requirements. Therefore, it is expected to develop a photocurable material with low viscosity, good aging resistance, excellent bendability and low dielectric performance requirements to solve the above technical problems. Summary of the invention
[0006] To overcome at least one of the defects of the prior art, in a first aspect, an embodiment of the present invention provides a photocurable film composition, including a fluorine-substituted cycloalkyl acrylate, a chain acrylate and an aromatic acrylate;
[0007] Wherein, the fluorine-substituted cycloalkyl acrylate has the following structure:
[0008]
[0009] R1 is a hydrogen atom or a methyl group; R2 is a methylene group, an ethoxy group or a propoxy group; R3 is a cyclohexyl group or a hexahydroindanyl group containing one or more substituents, wherein the one or more substituents include a C1-C6 fluoroalkyl group; n is an integer selected from 0 to 6;
[0010] The chain acrylate comprises one or two (meth) acrylic acid groups and an ester alkyl group connected to the (meth) acrylic acid group, wherein the ester alkyl group is a substituted or unsubstituted alkyl or alkylene group containing 3 to 30 carbon atoms, or the ester alkyl group is a polyoxyethylene ether segment.
[0011] In a second aspect, an embodiment of the present invention provides a photocurable film, which is obtained by photocuring a curing raw material, wherein the curing raw material includes the photocurable film composition described above.
[0012] In a third aspect, an embodiment of the present invention provides an organic electroluminescent device, comprising the above-mentioned photocurable film.
[0013] In a fourth aspect, an embodiment of the present invention provides use of the above-mentioned photocurable film composition or the above-mentioned photocurable film in display device packaging.
[0014] In a fifth aspect, an embodiment of the present invention provides a fluorine-substituted cycloalkyl acrylate having the following structure:
[0015]
[0016] R1 is a hydrogen atom or a methyl group; R2 is a methylene group, an ethoxy group or a propoxy group; R3 is a cyclohexyl group or a hexahydroindanyl group containing one or more substituents, wherein the one or more substituents include a C1-C6 fluoroalkyl group; and n is an integer selected from 0 to 6.
[0017] A photocurable film composition according to one embodiment of the present invention can be used to prepare a packaging film for display device packaging, which can enable the prepared film to have excellent curing rate, light transmittance, bending resistance, high elongation at break and low dielectric constant, which helps to improve the sealing and electrical insulation of the device. DETAILED DESCRIPTION
[0018] Typical embodiments that embody the features and advantages of the present invention will be described in detail in the following description. It should be understood that the present invention can have various changes in different embodiments without departing from the scope of the present invention, and the descriptions therein are essentially used as illustrations rather than to limit the present invention.
[0019] One embodiment of the present invention provides a photocurable film composition, including fluorine-substituted cycloalkyl acrylate, chain acrylate and aromatic acrylate;
[0020] Among them, the fluorine-substituted cycloalkyl acrylate has the following structure:
[0021]
[0022] R1 is a hydrogen atom or a methyl group; R2 is a methylene group, an ethoxy group or a propoxy group; R3 is a cyclohexyl group or a hexahydroindanyl group containing one or more substituents, wherein the one or more substituents include a C1-C6 fluoroalkyl group; n is an integer selected from 0 to 6;
[0023] The chain acrylate includes one or two (meth) acrylic acid groups and an ester alkyl group connected to the (meth) acrylic acid group. The ester alkyl group is a substituted or unsubstituted alkyl or alkylene group containing 3 to 30 carbon atoms, or the ester alkyl group is a polyoxyethylene ether segment.
[0024] A photocurable film composition according to an embodiment of the present invention can be used to prepare a packaging film for device packaging, wherein the use of fluorine-substituted cycloalkyl acrylate can not only reduce the dielectric constant of the prepared film, but also the higher bond energy of the CF bond can give the material higher stability; in addition, both fluorine-substituted cycloalkyl acrylate and chain acrylate can provide better flexibility, so that the film has better bending resistance; aromatic acrylate can provide a higher glass transition temperature and stronger hardness, thereby improving the strength of the film.
[0025] In one embodiment, n is an integer selected from 0 to 6, for example, n can be 0, 1, 2, 3, 4, 5 or 6.
[0026] In one embodiment, the one or more substituents in R3 include one or two C2-C5 fluoroalkyl groups and optionally C1-C2 alkyl groups (methyl and / or ethyl).
[0027] In one embodiment, the fluoroalkyl group in R3 may contain 2, 3, 4 or 5 carbon atoms.
[0028] In one embodiment, the fluoroalkyl group in R3 contains 3 to 5 fluorine atoms, such as 3, 4 or 5 fluorine atoms.
[0029] In one embodiment, the fluoroalkyl group in R3 may be selected from trifluoroethane, trifluoropropane, trifluorobutane, perfluoroethane and pentafluorobutane.
[0030] In one embodiment, the fluoroalkyl group in R3 may be selected from -CH2CF3, -CH2CH2CF3, -CH2CH2CH2CF3, -CH2CH2CF2CF3.
[0031] In one embodiment, the cyclohexyl or hexahydroindanyl group of R3 contains one or two fluorinated alkyl groups.
[0032] In another embodiment, the cyclohexyl or hexahydroindanyl group of R3 contains one or two fluoroalkyl groups and one methyl group.
[0033] In one embodiment, the fluorine-substituted cycloalkyl acrylate has the structure:
[0034]
[0035] R3 is a cyclohexyl or hexahydroindanyl group containing one or more substituents, wherein the one or more substituents include one or two C2-C5 fluoroalkyl groups and optionally C1-C2 alkyl groups (such as methyl groups), and the fluoroalkyl group contains 3-5 fluorine atoms.
[0036] In one embodiment, the fluorine-substituted cycloalkyl acrylate is selected from one or more of the following compounds:
[0037]
[0038]
[0039]
[0040]
[0041]
[0042] .
[0043] In one embodiment, the number of carbon atoms contained in the ester alkyl group of the linear acrylate may be 3-30, and further may be 3-18, for example 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 20, 22, 25 or 28.
[0044] In one embodiment, the substituent in the ester alkyl group of the linear acrylate may be a hydroxyl group and / or an oxo group (—O—).
[0045] In one embodiment, the chain acrylate includes one or two acrylic acid groups, or one or two methacrylic acid groups, wherein the acrylic acid group is CH2=CHCOO-, and the methacrylic acid group is CH2=C(CH3)COO-.
[0046] In one embodiment, the structural formula of the chain acrylate is CH2=CHCOO-R4 or CH2=C(CH3)COO-R4, and R4 is a substituted or unsubstituted alkyl group containing 3 to 30 carbon atoms. Further, R4 can be a substituted or unsubstituted straight-chain alkyl group or a branched-chain alkyl group.
[0047] In one embodiment, the structural formula of the chain acrylate is CH2=CHCOO-R5-OOCCH=CH2 or CH2=C(CH3)COO-R5-OOCC(CH3)=CH2, and R5 is a substituted or unsubstituted alkylene group containing 3 to 30 carbon atoms. Further, R5 can be a substituted or unsubstituted straight chain alkylene group or a branched chain alkylene group.
[0048] In one embodiment, the linear acrylate containing one (meth)acrylic acid group may be an alkyl (meth)acrylate, such as butyl (meth)acrylate, hexyl (meth)acrylate, propyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate (e.g., isodecyl (meth)acrylate), dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate (e.g., isooctadecyl (meth)acrylate), eicosyl (meth)acrylate, behenyl (meth)acrylate; or may be a (meth)acrylate containing a hydroxyl group or an oxygen atom, such as butoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate.
[0049] In one embodiment, the chain acrylate containing two (meth)acrylic groups includes one or more of neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol diacrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, and 1,14-dodecanediol di(meth)acrylate.
[0050] In one embodiment, the linear acrylate is selected from dodecyl acrylate, 1,12-dodecanediol dimethacrylate and / or 1,6-hexanediol dimethacrylate.
[0051] In one embodiment, the aromatic acrylate includes a substituted or unsubstituted benzene ring group, a substituted or unsubstituted naphthalene ring group, or a substituted or unsubstituted anthracene ring group.
[0052] In one embodiment, the aromatic acrylate may include one or more of o-phenylphenoxyethyl (meth) acrylate (e.g., 2-([1,1'-biphenyl]-2-oxy)ethyl 2-acrylate or (2-ethoxy) o-phenylphenoxyethyl acrylate), benzyl (meth) acrylate, (2-ethoxy)phenol acrylate, (2-propoxy)nonylphenol acrylate, 3-phenoxybenzyl acrylate, 2-phenoxyethyl (meth) acrylate, and 2-hydroxy-3-phenoxypropyl 2-(meth) acrylate.
[0053] In one embodiment, the photocurable film composition includes 10 to 50 parts by mass of fluorine-substituted cycloalkyl acrylate, 15 to 60 parts by mass of chain acrylate, and 5 to 30 parts by mass of aromatic acrylate. For example, the content of fluorine-substituted cycloalkyl acrylate in the photocurable film composition can be 20 parts by mass, 22 parts by mass, 25 parts by mass, 27 parts by mass, 30 parts by mass, 32 parts by mass, 35 parts by mass, 37 parts by mass, 40 parts by mass, 45 parts by mass, or 47 parts by mass; the content of chain acrylate can be 20 parts by mass, 25 parts by mass, 30 parts by mass, 35 parts by mass, 40 parts by mass, 45 parts by mass, 50 parts by mass, or 55 parts by mass; and the content of aromatic acrylate can be 10 parts by mass, 15 parts by mass, 20 parts by mass, or 25 parts by mass.
[0054] In one embodiment, the photocurable film composition includes 25 to 50 parts by mass of fluorine-substituted cycloalkyl acrylate, 35 to 40 parts by mass of linear acrylate, and 20 to 30 parts by mass of aromatic acrylate.
[0055] In one embodiment, the photocurable film composition includes a fluorine-substituted cycloalkyl acrylate, a linear acrylate, an aromatic acrylate, and a photoinitiator.
[0056] In one embodiment, the photocurable film composition includes fluorine-substituted cycloalkyl acrylate, linear acrylate, aromatic acrylate, a photoinitiator, and an auxiliary agent.
[0057] In one embodiment, the photocurable film composition includes 10 to 50 parts by mass of fluorine-substituted cycloalkyl acrylate, 15 to 60 parts by mass of chain acrylate, 5 to 30 parts by mass of aromatic acrylate, 1 to 5 parts by mass of photoinitiator and 0 to 5 parts by mass of auxiliary agent. For example, the content of the photoinitiator in the photocurable film composition can be 1.5 parts by mass, 2 parts by mass, 3 parts by mass or 4 parts by mass; the content of the auxiliary agent can be 0.1 parts by mass, 0.5 parts by mass, 1 part by mass, 2 parts by mass, 3 parts by mass or 4 parts by mass.
[0058] In one embodiment, the photoinitiator is a free radical photoinitiator, including one or more of benzoin and its derivatives, benzil and its derivatives, acetophenone derivatives, α-amino ketone derivatives, acylphosphine oxides and sulfur-containing initiators.
[0059] In one embodiment, the photoinitiator may include one or more of α,α′-dimethoxy-α-phenylacetophenone, α,α-diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, hydroxycyclohexane phenone, 2-methyl-4-methylthio-2-morpholinophenylpropiophenone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and methyl phenylacetophenone.
[0060] In one embodiment, since UV-LED lamps with wavelengths above 365 nm are mostly used in the industry, it is suitable to use a photoinitiator with strong absorbance for light with wavelengths above 365 nm, such as one or more of diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (trade name TPO), ethyl 2,4,6-trimethylbenzoyl phenylphosphonate (trade name TPO-L), and phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide (trade name 819).
[0061] In one embodiment, the auxiliary agent includes one or more of a surfactant, a defoamer, a dispersant, a leveling agent, an adhesion promoter, a thermal stabilizer and an inhibitor. Further, the surfactant may be one or more of the surfactants produced by BYK Chemical (e.g., BYK-300, BYK302, BYK358N, BYK361N) and the surfactants produced by Shin-Etsu Chemical (e.g., KP341 and KP310); the adhesion promoter may be 3-(isomethacryloyloxy)propyltrimethoxysilane and / or (3-mercaptopropyl)trimethoxysilane; the thermal stabilizer may be pentaerythritol tetra(3-(3,5-di-tert-butyl-4-hydroxyphenyl)acrylate) and / or 1,3,5-tris(2-hydroxyethyl)isocyanurate.
[0062] In one embodiment, the photocurable film composition is in the form of a photocurable adhesive.
[0063] In one embodiment, the preparation method of the photocurable adhesive includes: adding fluorine-substituted cycloalkyl acrylate, chain acrylate, aromatic acrylate, photoinitiator and optional auxiliary agent into a reaction kettle according to the aforementioned mass parts, stirring at 20-50° C. for 30-60 minutes to mix the components evenly, and obtaining a photocurable adhesive with a viscosity of 5-50 cps.
[0064] In one embodiment, the viscosity of the photocurable adhesive is 5 to 50 cps, such as 8 cps, 10 cps, 15 cps, 16 cps, 16.5 cps, 17 cps, 17.5 cps, 18 cps, 18.5 cps, 19 cps, 20 cps, 25 cps, 30 cps, 35 cps, 40 cps, and 45 cps. The viscosity is measured by a viscometer at 25°C.
[0065] In one embodiment, the viscosity of the photocurable adhesive may be 15 to 20 cps, and further may be 16 to 19 cps.
[0066] In one embodiment, the surface tension of the photocurable adhesive may be 20 to 30 mN / m, and may further be 23 to 27 mN / m, for example, 23.5 mN / m, 24 mN / m, 24.5 mN / m, 25 mN / m, 25.5 mN / m, 26 mN / m, and 26.5 mN / m.
[0067] An embodiment of the present invention provides a photocurable film, which is obtained by photocuring raw materials through a photocuring reaction, and the curing raw materials include the above-mentioned photocurable film composition.
[0068] In one embodiment, the photocurable composition can be cured using a commonly used ultraviolet light source at relatively low energy.
[0069] In one embodiment, the light transmittance of the photocurable film is 98-99.5%, for example, 98.5% or 99%.
[0070] In one embodiment, the elongation at break of the photocured film is 9-12%, for example, 9.5%, 10%, 10.5%, 11%, or 11.5%.
[0071] In one embodiment, the dielectric constant of the photocured film is 2.5 to 2.7, for example, 2.55, 2.57, 2.58, 2.6, 2.61, 2.62, 2.63, 2.66, or 2.68.
[0072] An embodiment of the present invention provides a display device, comprising the above-mentioned photocurable film. Furthermore, the display device may be an organic electroluminescent device.
[0073] One embodiment of the present invention provides the use of the above-mentioned photocurable film composition or photocurable film in display device packaging, especially in packaging of organic electroluminescent devices.
[0074] A photocurable film composition according to an embodiment of the present invention can be used to prepare a packaging film for display device (e.g., organic electroluminescent device) packaging, which can enable the prepared film to have good bending resistance, aging resistance, and a low dielectric constant, help improve the sealing and electrical insulation of the device, and can effectively extend the life and stability of the device.
[0075] A photocurable film composition according to one embodiment of the present invention, such as a photocurable adhesive, has appropriate viscosity and surface tension and good inkjet printing performance; at the same time, the film obtained after curing has excellent curing rate, light transmittance, bending resistance, high elongation at break and low dielectric constant.
[0076] The preparation and application of the photocurable film composition according to one embodiment of the present invention are further described below in conjunction with examples. The raw materials and test methods used in each example and comparative example are as follows:
[0077] raw material
[0078]
[0079] Test Method
[0080] 1. Viscosity
[0081] Take an appropriate amount of light-curing adhesive sample and add it to the viscometer (LV-SSR rotary viscometer), and test the viscosity of the sample at 25°C.
[0082] 2. Surface tension
[0083] 30 mL of photocuring adhesive sample was placed in a beaker, and the surface tension of the sample was tested using a bubble method surface tension meter (SITA pro line T15).
[0084] 3. Curing rate
[0085] The curing rate of the photocuring adhesive sample was tested using an FT-IR device (Thermo Fisher Nicolet iS5). The specific process was as follows: 1 mL of the photocuring adhesive sample was added between two release films, and then pressure was applied to spread the photocuring adhesive evenly on the release films. A UV-LED lamp with a wavelength of 395 nm was used to apply 1500 mJ / cm 2 The energy of the light-curing adhesive is cured into a film of 20-30 microns thick. The samples were tested before and after curing at 1635 cm -1 (C=C) and 1720cm -1 The intensity of the absorption peak near (C=O) was used to calculate the curing rate using the following formula:
[0086] Curing rate (%) = |1-(A / B)| × 100%
[0087] Where A represents the solidified film at 1635cm -1 and 1720cm -1 The intensity ratio of the absorption peaks near 1635cm -1 and 1720cm -1 The intensity ratio of nearby absorption peaks.
[0088] 4. Light transmittance
[0089] The photocurable adhesive was printed on the electronic glass substrate using an inkjet printer, and a UV-LED lamp with a wavelength of 395 nm was used to apply 1500 mJ / cm 2 The photocurable adhesive was cured into a 12 μm thick film with energy, and the light transmittance of the film was tested by a colorimeter (HunterLab UltraScan VIS).
[0090] 5. Bending performance
[0091] The photocurable adhesive was evenly coated on the PI film and a UV-LED lamp with a wavelength of 395 nm was used to apply 1500 mJ / cm 2 The photocurable adhesive was cured into a 12 μm thick film with energy. The bending performance of the PI film plus the photocurable film was tested at room temperature using a bending tester (IR=1.0). The result that passed the 200,000-times bending test was recorded as ○, and the result that failed the 200,000-times bending test was recorded as ✖.
[0092] 6. Elongation at break
[0093] The elongation at break was tested according to GB / T 1040-92 "General test methods for mechanical properties of plastics (tensile)". The instrument used was an MTS-C42 electronic universal testing machine. The tensile speed was set to 1 mm / min, the sample thickness was 12 μm, the gauge length was 50 mm, and each group of samples was tested 5 times to obtain the average value of the elongation at break.
[0094] 7. Double 85 aging
[0095] The photocurable adhesive was printed on the electronic glass substrate using an inkjet printer, and a UV-LED lamp with a wavelength of 395 nm was used to apply 1500 mJ / cm 2 The photocurable adhesive was cured into a 12μm thick film with energy, and the film was aged in a constant temperature and humidity chamber at 85℃ and 85% humidity for 504 hours to observe whether the film surface was cracked or wrinkled. The film surface that was well preserved was recorded as ○, and the film surface that was abnormal was recorded as ✖.
[0096] 8. Dielectric constant
[0097] The photocurable adhesive sample was printed on an ITO glass substrate using an inkjet printer, and a UV-LED lamp with a wavelength of 395 nm was used to apply 1500 mJ / cm 2 The photocurable adhesive sample was cured into a 12μm thick film using energy. Silver electrodes were prepared on the film using vacuum evaporation equipment to form a three-layer structure of ITO / film / silver. The capacitance of the cured film was tested using an impedance analyzer (Keysight Technologies, 4990A), and the dielectric constant was calculated using the following formula:
[0098]
[0099] Among them, C p is the equivalent parallel capacitance of the test film (F);
[0100] t m is the average thickness of the tested film (m);
[0101] A is the surface area of the electrode (m 2 );
[0102] d is the diameter of the electrode (m);
[0103] ε0 is the dielectric constant of free space = 8.854×10 -12 (F / m).
[0104] 9. Inkjet performance
[0105] The inkjet printing performance of the photocurable adhesive samples was tested by a piezoelectric drop-on-demand print head (KM1024i Konica Minolta). The inkjet head temperature was 25-35°C and the speed was 3μm / sec. Spherical droplets were formed during inkjet printing without ink flying. The results with good wettability were recorded as ○, and the results with abnormal inkjet printing were recorded as ✖.
[0106] Preparation Example 1
[0107] Preparation of intermediate 1
[0108] At -78°C, 47g (0.5mol) of phenol and an appropriate amount of dichloromethane, 57.6g (1.2eq, 0.6mol) of trifluoropropylene, 3.4g (0.1eq, 0.05mol) of boron trifluoride and 35g (3.5eq, 1.75mol) of hydrogen fluoride were slowly added to the flask in sequence and stirred evenly, then the temperature was raised to room temperature and stirred for 24h. After the reaction was completed, the reactants were poured into ice NaHCO3 for quenching, and the reaction liquid was extracted with dichloromethane to obtain an organic liquid. The organic liquid was washed with water three times until neutral, and then dried with anhydrous sodium sulfate. Then, dichloromethane was removed by rotary evaporator, and intermediate 1 was obtained by column chromatography with a purity of 96% and a yield of 63%. 1 H NMR (400 MHz, DMSO-d6): δ6.99(dt, J = 8.6, 1.1 Hz,1H), 6.75-6.67(m, 1H), 2.87-2.69(m, 1H), 2.46(qt, J = 9.0, 7.6 Hz, 1H).
[0109]
[0110] Preparation of intermediate 2
[0111] Using ruthenium dioxide as a catalyst, isopropanol and water as solvents, intermediate 1 was subjected to catalytic hydrogenation reaction at 10 MPa and 180°C for 4 h to obtain intermediate 2 with a yield of nearly 100%.
[0112] Preparation of compound of formula 3
[0113] Under nitrogen atmosphere, add 29.4g (0.15mol) of intermediate 2 and dichloromethane to the flask and stir until dissolved; then cool the resulting solution to 0°C, and add triethylamine to it; slowly add a dichloromethane solution of acryloyl chloride (1.1eq, 14.9g, 0.165mol) to the system through a constant pressure funnel at 0°C. After the addition is complete, raise the system temperature to room temperature and continue stirring for 10h until the reaction is completed. Wash the reaction solution with water until it is neutral, add anhydrous sodium sulfate to dry the reaction solution, remove dichloromethane using a rotary evaporator, and separate and purify the resulting substance by column chromatography to obtain a colorless and transparent product with a purity of 98% and a yield of 84%. 1 H NMR (400 MHz, DMSO-d6): δ 6.16-6.01 (m, 3H), 4.78(p,J=4.8Hz, 1H), 2.28(tq, J=10.6, 9.0 Hz, 2H), 1.94-1.82(m, 2H), 1.74-1.53(m,4H), 1.52-1.36(m, 4H).
[0114]
[0115] Preparation Example 2
[0116] Preparation of intermediate 3
[0117] At -78°C, 47g (0.5mol) of phenol and an appropriate amount of dichloromethane, 87.6g (1.2eq, 0.6mol) of 3,3,4,4,4-pentafluorobutene, 3.4g (0.1eq, 0.05mol) of boron trifluoride and 35g (3.5eq, 1.75mol) of hydrogen fluoride were slowly added to the flask in sequence and stirred evenly, then the temperature was raised to room temperature and stirred for 24h. After the reaction was completed, the reactants were poured into ice NaHCO3 for quenching, and the reaction liquid was extracted with dichloromethane to obtain an organic liquid. The organic liquid was washed with water three times until neutral, and then dried with anhydrous sodium sulfate. The dichloromethane was removed by a rotary evaporator, and then the intermediate 3 was obtained by column chromatography with a purity of 94% and a yield of 52%. 1 H NMR (400 MHz, DMSO-d6): δ 6.99 (dt, J=8.5,1.1Hz, 1H), 6.74-6.67(m, 1H), 2.78 (tt, J = 9.7, 0.9Hz, 1H), 2.61-2.28(m,1H).
[0118]
[0119] Preparation of intermediate 4
[0120] Using ruthenium dioxide as a catalyst, isopropanol and water as solvents, intermediate 3 was subjected to catalytic hydrogenation reaction at 10 MPa and 180°C for 4 h to obtain intermediate 4 with a yield of nearly 100%.
[0121] Preparation of compound of formula 8
[0122] Under nitrogen atmosphere, 36.9 g (0.15 mol) of intermediate 4 and dichloromethane were added to the flask and stirred until dissolved; then the resulting solution was cooled to 0°C, and triethylamine was added thereto; at 0°C, a dichloromethane solution of methacryloyl chloride (1.1 eq, 17.2 g, 0.165 mol) was slowly added dropwise to the system through a constant pressure funnel. After the addition was complete, the system temperature was raised to room temperature and continued to stir for 10 h until the reaction was completed. The reaction solution was washed with water until neutral, and then anhydrous sodium sulfate was added to dry the reaction solution. The dichloromethane was removed by a rotary evaporator, and the resulting substance was separated and purified by column chromatography to obtain a colorless transparent product with a purity of 96% and a yield of 89%. 1H NMR (400 MHz, DMSO-d6): δ 5.86(p, J = 1.5 Hz,1H), 5.77 – 5.71(m, 1H), 4.75(p, J = 5.3 Hz, 1H), 2.16 (tt, J = 20.9, 8.8 Hz,2H), 1.96-1.81(m, 5H), 1.74-1.34(m, 9H).
[0123]
[0124] Preparation Example 3
[0125] Preparation of intermediate 5
[0126] At -78°C, 54g (0.5mol) of 4-methylphenol and an appropriate amount of dichloromethane, 115.2g (2.4eq, 1.2mol) of trifluoropropylene, 5.1g (0.15eq, 0.075mol) of boron trifluoride and 53g (5.25eq, 2.63mol) of hydrogen fluoride were slowly added to the flask in sequence and stirred evenly, then the temperature was raised to room temperature and stirred for 24h. After the reaction was completed, the reactants were poured into ice NaHCO3 for quenching, and the reaction liquid was extracted with dichloromethane to obtain an organic liquid. The organic liquid was washed with water three times until neutral, and then dried with anhydrous sodium sulfate. Then, dichloromethane was removed by rotary evaporator, and intermediate 5 was obtained by column chromatography with a purity of 94% and a yield of 67%. 1 H NMR (400 MHz, DMSO-d6): δ 6.82(s, 1H), 2.58(ddt, J =8.1, 7.1, 1.1 Hz, 2H), 2.54-2.42(m, 2H).
[0127]
[0128] Preparation of intermediate 6
[0129] Using ruthenium dioxide as a catalyst, isopropanol and water as solvents, intermediate 5 was subjected to catalytic hydrogenation reaction at 10 MPa and 180°C for 4 h to obtain intermediate 6 with a yield of nearly 100%.
[0130] Preparation of compound of formula 10
[0131] Under nitrogen atmosphere, 46.1g (0.15mol) of intermediate 6 and dichloromethane were added to the flask and stirred until dissolved; then the resulting solution was cooled to 0°C, triethylamine was added thereto, and a dichloromethane solution of methacryloyl chloride (1.1eq, 17.2g, 0.165mol) was slowly added to the system through a constant pressure funnel at 0°C. After the addition was completed, the system temperature was raised to room temperature and continued to stir for 10h until the reaction was completed. The reaction solution was washed with water until neutral, and then anhydrous sodium sulfate was added to dry the reaction solution. The dichloromethane was removed by a rotary evaporator, and the resulting substance was separated and purified by column chromatography to obtain a colorless and transparent product with a purity of 97% and a yield of 85%. 1 H NMR (400 MHz, DMSO-d6): δ 5.94(p, J = 1.5 Hz, 1H), 5.70(p, J = 1.5 Hz, 1H), 4.63(d, J = 13.0 Hz, 1H), 2.33-2.16(m, 4H), 2.07(tq, J = 9.6, 6.9 Hz, 2H), 1.94(t, J = 1.3 Hz, 3H), 1.71-1.44(m, 6H), 1.35(dt, J = 12.3, 7.0 Hz, 2H), 0.90(d, J = 6.6 Hz, 3H).
[0132]
[0133] Preparation Example 4
[0134] Preparation of intermediate 7
[0135] At -78°C, 67g (0.5mol) of 2-indanol and an appropriate amount of dichloromethane, 57.6g (1.2eq, 0.6mol) of trifluoropropylene, 3.4g (0.1eq, 0.05mol) of boron trifluoride and 35g (3.5eq, 1.75mol) of hydrogen fluoride were slowly added to the flask in sequence and stirred evenly, then the temperature was raised to room temperature and stirred for 24h. After the reaction was completed, the reactants were poured into ice NaHCO3 for quenching, and the reaction liquid was extracted with dichloromethane to obtain an organic liquid. The organic liquid was washed with water three times until neutral, and then dried with anhydrous sodium sulfate. Then, dichloromethane was removed by rotary evaporator, and intermediate 7 was obtained by column chromatography with a purity of 97% and a yield of 59%. 1H NMR (400MHz, DMSO-d6): δ 7.10-6.96(m, 3H), 4.22(p, J= 5.6 Hz, 1H), 3.10-2.94 (m, 3H), 2.89(ddd, J = 12.4, 5.9, 1.1 Hz, 1H), 2.81-2.64 (m, 2H), 2.56-2.37(m, 2H).
[0136]
[0137] Preparation of intermediate 8
[0138] Using ruthenium dioxide as a catalyst, isopropanol and water as solvents, intermediate 7 was subjected to catalytic hydrogenation reaction at 10 MPa and 180°C for 4 h to obtain intermediate 8 with a yield of nearly 100%.
[0139] Preparation of compound of formula 13
[0140] Under nitrogen atmosphere, 35.4 g (0.15 mol) of intermediate 8 and dichloromethane were added to the flask and stirred until dissolved; then the solution was cooled to 0°C and triethylamine was added thereto; a dichloromethane solution of acryloyl chloride (1.1 eq, 14.9 g, 0.165 mol) was slowly added to the system through a constant pressure funnel at 0°C. After the addition was completed, the system temperature was raised to room temperature and continued to stir for 10 hours until the reaction was completed. The reaction solution was washed with water until neutral, and then anhydrous sodium sulfate was added to dry the reaction solution. The dichloromethane was removed by a rotary evaporator, and the obtained substance was separated and purified by column chromatography to obtain a colorless transparent product with a purity of 96% and a yield of 85%. 1 H NMR (400 MHz, DMSO-d6): δ 6.16-6.00(m, 3H), 4.97 (p, J =5.1 Hz, 1H), 2.31 – 2.14 (m, 2H), 2.11- 2.01(m, 2H), 1.87(dtd, J = 12.2, 5.2,3.2 Hz, 2H), 1.79-1.21(m, 11H).
[0141]
[0142] Example 1
[0143] 35 parts by mass of dodecyl acrylate (A1), 25 parts by mass of 3-phenoxybenzyl acrylate (B1), 37 parts by mass of the compound of formula 3 (C1) obtained in Preparation Example 1, and 3 parts by mass of TPO initiator were added to a homogenizer, and stirred at a speed of 1500 r / min at room temperature for 30 min under light-proof conditions to obtain a uniformly mixed photocurable adhesive.
[0144] Example 2
[0145] 40 parts by mass of dodecyl acrylate (A1), 25 parts by mass of o-phenylphenoxyethyl acrylate (B2), 32 parts by mass of the compound of formula 8 (C2) obtained in Preparation Example 2, and 3 parts by mass of TPO initiator were added to a homogenizer, and stirred at a speed of 1500 r / min at room temperature for 30 minutes under light-proof conditions to obtain a uniformly mixed photocurable adhesive.
[0146] Example 3
[0147] 35 parts by mass of 1,6-hexanediol dimethacrylate (A2), 30 parts by mass of 3-phenoxybenzyl acrylate (B1), 32 parts by mass of the compound of formula 10 (C3) obtained in Preparation Example 3, and 3 parts by mass of TPO initiator were added to a homogenizer, and stirred at a speed of 1500 r / min at room temperature for 30 minutes under light-proof conditions to obtain a uniformly mixed photocurable adhesive.
[0148] Example 4
[0149] 40 parts by mass of 1,12-dodecanediol dimethacrylate (A3), 30 parts by mass of 3-phenoxybenzyl acrylate (B1), 27 parts by mass of the compound of formula 13 (C4) obtained in Preparation Example 4, and 3 parts by mass of TPO initiator were added to a homogenizer, and stirred at a speed of 1500 r / min at room temperature for 30 minutes under light-proof conditions to obtain a uniformly mixed photocurable adhesive.
[0150] Example 5
[0151] 35 parts by mass of dodecyl acrylate (A1), 20 parts by mass of 2-acrylic acid-2-hydroxy-3-phenoxypropyl ester (B3), 20 parts by mass of the compound of formula 3 (C1) obtained in Preparation Example 1, 22 parts by mass of the compound of formula 10 (C3) obtained in Preparation Example 3 and 3 parts by mass of TPO initiator were added to a homogenizer, and stirred at a speed of 1500 r / min at room temperature for 30 minutes under light-proof conditions to obtain a uniformly mixed photocurable adhesive.
[0152] Example 6
[0153] 35 parts by mass of 1,12-dodecanediol dimethacrylate (A3), 20 parts by mass of 3-phenoxybenzyl acrylate (B1), 20 parts by mass of the compound of formula 8 (C2) obtained in Preparation Example 2, 27 parts by mass of the compound of formula 13 (C4) obtained in Preparation Example 4, and 3 parts by mass of TPO initiator were added to a homogenizer, and stirred at a speed of 1500 r / min at room temperature for 30 minutes under light-proof conditions to obtain a uniformly mixed photocurable adhesive.
[0154] Example 7
[0155] 20 parts by mass of dodecyl acrylate (A1), 20 parts by mass of 1,6-hexanediol dimethacrylate (A2), 25 parts by mass of 3-phenoxybenzyl acrylate (B1), 32 parts by mass of the compound of formula 3 (C1) obtained in Preparation Example 1, and 3 parts by mass of TPO initiator were added to a homogenizer, and stirred at a speed of 1500 r / min at room temperature for 30 min under light-proof conditions to obtain a uniformly mixed photocurable adhesive.
[0156] Comparative Example 1
[0157] 35 parts by mass of dodecyl acrylate (A1), 25 parts by mass of 3-phenoxybenzyl acrylate (B1), 37 parts by mass of C5 compound and 3 parts by mass of TPO initiator were added into a homogenizer, and stirred at a speed of 1500 r / min at room temperature for 30 min under light-proof conditions to obtain a uniformly mixed photocurable adhesive.
[0158] Among them, the C5 compound is 1H,1H-heptafluoromethylacrylate, and its structural formula is as follows:
[0159]
[0160] Comparative Example 2
[0161] 35 parts by mass of 1,6-hexanediol dimethacrylate (A2), 30 parts by mass of o-phenylphenoxyethyl acrylate (B2), 32 parts by mass of C6 compound and 3 parts by mass of TPO initiator were added into a homogenizer, and stirred at a speed of 1500 r / min at room temperature for 30 minutes under light-proof conditions to obtain a uniformly mixed photocurable adhesive.
[0162] Among them, the C6 compound is 2-(perfluorooctyl)ethyl methacrylate, and its structural formula is as follows:
[0163]
[0164] Comparative Example 3
[0165] 35 parts by mass of 1,12-dodecanediol dimethacrylate (A3), 25 parts by mass of 3-phenoxybenzyl acrylate (B1), 37 parts by mass of C7 compound and 3 parts by mass of TPO initiator were added into a homogenizer, and stirred at a speed of 1500 r / min at room temperature for 30 min under light-proof conditions to obtain a uniformly mixed photocurable adhesive.
[0166] Wherein, the C7 compound is 3-trifluoromethyl-1-adamantane acrylate, and its structural formula is as follows:
[0167]
[0168] Comparative Example 4
[0169] 35 parts by mass of 1,6-hexanediol dimethacrylate (A2), 30 parts by mass of 3-phenoxybenzyl acrylate (B1), 32 parts by mass of C8 compound and 3 parts by mass of TPO initiator were added into a homogenizer, and stirred at a speed of 1500 r / min at room temperature for 30 min under light-proof conditions to obtain a uniformly mixed photocurable adhesive.
[0170] Among them, the C8 compound is 3,5-bis(trifluoromethyl)-1-adamantane acrylate, and its structural formula is as follows:
[0171]
[0172] Comparative Example 5
[0173] 35 parts by mass of dodecyl acrylate (A1), 25 parts by mass of 2-acrylate-2-hydroxy-3-phenoxypropyl ester (B3), 37 parts by mass of compound D and 3 parts by mass of TPO initiator were placed in a homogenizer, stirred at a speed of 1500 r / min at room temperature for 30 minutes under light-proof conditions to obtain a uniformly mixed photocurable adhesive.
[0174] Wherein, compound D is cyclohexyl acrylate, and its structural formula is as follows:
[0175]
[0176] Table 1 lists the types and amounts (parts by mass) of the raw materials used in each embodiment and comparative example. The light-curing adhesives prepared in each embodiment and comparative example were tested for relevant properties according to the aforementioned method, and the results are shown in Table 2.
[0177] Table 1 Types and amounts of raw materials used in various examples and comparative examples
[0178]
[0179] Table 2 Performance test results of the photocurable adhesive and film of each embodiment and comparative example
[0180]
[0181] According to the results in Table 2, the photocurable compositions (photocurable adhesives) of Examples 1 to 7 of the present invention have appropriate viscosity and surface tension, and good inkjet printing performance; and the prepared films have excellent curing rate, light transmittance, bending resistance and aging resistance, lower dielectric constant and higher elongation at break.
[0182] Although some of the photocurable films in Comparative Examples 1 to 5 also have better bending performance and lower dielectric constant, they cannot achieve comprehensive optimization of bending resistance, light transmittance, elongation at break, etc. Specifically, Comparative Examples 1 and 2 use chain fluorine-containing acrylates. Although the films obtained can achieve the purpose of reducing the dielectric constant, the photocurable adhesive cannot meet the requirements of aging resistance and inkjet printing. Comparative Examples 3 and 4 use adamantane-type fluorine-containing acrylates to prepare photocurable films. Since the adamantane group has greater rigidity, the elongation at break of the samples is lower and the bending resistance is poor; and the inkjet printing performance of the photocurable adhesive is also poor. Comparative Example 5 uses fluorine-free cyclohexane acrylates. The dielectric constant of the film obtained is higher and the bending resistance is poor.
[0183] Unless otherwise defined, the terms used in the present invention have the meanings commonly understood by those skilled in the art.
[0184] The embodiments described in the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Those skilled in the art may make various other substitutions, changes and improvements within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments, but is only limited by the claims.
Claims
1. A photocurable film composition, characterized in that: The invention comprises 10 to 50 parts by weight of fluorine-substituted cycloalkyl acrylate, 15 to 60 parts by weight of chain acrylate, 5 to 30 parts by weight of aromatic acrylate and a photoinitiator; Wherein, the fluorine-substituted cycloalkyl acrylate has the following structure: R1 is a hydrogen atom or a methyl group; R2 is a methylene group, an ethoxy group or a propoxy group; R3 is a cyclohexyl group or a hexahydroindanyl group containing one or more substituents, wherein the one or more substituents include a C1-C6 fluoroalkyl group; n is an integer selected from 0 to 6; The chain acrylate comprises one or two (meth) acrylic acid groups and an ester alkyl group connected to the (meth) acrylic acid group, wherein the ester alkyl group is a substituted or unsubstituted alkyl or alkylene group containing 3 to 30 carbon atoms, or the ester alkyl group is a polyoxyethylene ether segment.
2. The photocurable film composition according to claim 1, characterized in that: The fluorine-substituted cycloalkyl acrylate has the following structure: R3 is a cyclohexyl or hexahydroindanyl group containing one or more substituents, wherein the one or more substituents in R3 include one or two C2-C5 fluoroalkyl groups and optionally C1-C2 alkyl groups, wherein the fluoroalkyl groups contain 3-5 fluorine atoms; and / or, The optional substituent in the ester alkyl group of the linear acrylic ester is a hydroxyl group and / or an oxo group.
3. The photocurable film composition according to claim 1 or 2, characterized in that: The fluoroalkyl group is selected from one or more of a trifluoroethane group, a trifluoropropane group, a trifluorobutane group, a perfluoroethane group and a pentafluorobutane group; and / or, The chain acrylate includes one or more of the following compounds: CH2=CHCOO-R4, CH2=C(CH3)COO-R4, CH2=CHCOO-R5-OOCCH=CH2, CH2=C(CH3)COO-R5-OOCC(CH3)=CH2; Among them, R4 is a substituted or unsubstituted straight-chain alkyl or branched alkyl group containing 3 to 18 carbon atoms, and the substituent is a hydroxyl group and / or an oxo group; R5 is a straight-chain alkylene group containing 3 to 18 carbon atoms or a branched alkylene group.
4. The photocurable film composition according to claim 1, characterized in that: The fluorine-substituted cycloalkyl acrylate is selected from one or more of the following compounds: 。 5. The photocurable film composition according to claim 1, characterized in that: The chain acrylates include butyl (meth)acrylate, hexyl (meth)acrylate, propyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, eicosyl (meth)acrylate, behenyl (meth)acrylate, butoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, Ester, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol diacrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, 1,14-dodecanediol di(meth)acrylate; and / or, The aromatic acrylate includes one or more of o-phenylphenoxyethyl (meth) acrylate, benzyl (meth) acrylate, (2-ethoxy)phenol acrylate, (2-propoxy)nonylphenol acrylate, 3-phenoxybenzyl acrylate, (meth) acrylate-2-phenoxyethyl ester, 2-(meth) acrylate-2-hydroxy-3-phenoxypropyl ester; and / or, The photocurable film composition comprises 25 to 50 parts by mass of the fluorine-substituted cycloalkyl acrylate, 35 to 40 parts by mass of the chain acrylate and 20 to 30 parts by mass of the aromatic acrylate; and / or, The photocurable film composition comprises 1 to 5 parts by weight of the photoinitiator and 0 to 5 parts by weight of an auxiliary agent.
6. The photocurable film composition according to claim 5, characterized in that: The photoinitiator comprises one or more of benzoin and its derivatives, benzil and its derivatives, acetophenone derivatives, α-aminoketone derivatives, acylphosphine oxides and sulfur-containing initiators; and / or, The auxiliary agent includes one or more of a surfactant, a defoamer, a dispersant, a leveling agent, an adhesion promoter, a heat stabilizer and an inhibitor.
7. A photocurable film, obtained by photocuring raw materials through a photocuring reaction, characterized in that: The curing raw material includes the photocurable film composition according to any one of claims 1 to 6.
8. An organic electroluminescent device, characterized in that: The photocurable film according to claim 7 is included.
9. Use of the photocurable film composition according to any one of claims 1 to 6 or the photocurable film according to claim 7 in display device packaging.
Citation Information
Patent Citations
Fluorine-contained surfactant and preparation method thereof
CN102172491A
Compound, resin, resist composition and method for producing resist pattern
TW201616220A
Pattern formation method, active light sensitive or radiation sensitive composition, and electronic device production method
WO2021199789A1